Suggestopedia-Based Language Learning to Enhance Students’ Speaking Skills Viewed from Teachers’ Educational Background - Muhammad Syarifuddin; Muhammad Muhlisin; Vu Tien Thinh (Journal of Language and Literature Studies, 2022)
Speaking skills are nowadays more promising skills economically to be learnt. The importance of mastering speaking skills shows that teachers should find a good solution to encourage their students to practice speaking much more. One of the learning models applied by teachers is suggestopedia-based language learning (SBLL) activities. Therefore, this study investigated the effectiveness of suggestopedia-based language learning to enhance students’ speaking skills viewed from teachers’ educational backgrounds at middle schools. To achieve the research goal, researchers employed experimental study using an equivalent pre-test and post-test control group design. The samples of this study were 75 students at middle schools, and they were divided into two classes. 33 students were involved as the experimental class subjected to the SBLL activities. 32 students were invited as the control classes, which was taught using the existing instructional activities (eclectic learning principles). The two groups were distributed speaking tests in the pre-test and post-test sessions. The variable of teachers’ educational background is assumed as helping variable that gives an effect on students’ speaking ability. The criteria used in this case are Very High (Educational Doctor) High (Educational Master), Moderate (Educational Bachelor), and Low (Non-educational Bachelor). The research findings of this study informed that the implementation of the SBLL has positive effects on speaking skills at middle schools. Furthermore, there is interaction between teachers’ educational background and the use of the SBLL in improving students’ speaking skills at middle schools. Therefore, this study can be concluded that the use of the SBLL was able to enhance students’ speaking skills viewed from teachers’ educational backgrounds at the middle schools.